2012
DOI: 10.1177/1367493512456106
|View full text |Cite
|
Sign up to set email alerts
|

Family factors associated with children's handwashing hygiene behavior

Abstract: Despite the importance of children's hand hygiene and family influence on children's behaviors, few studies have been dedicated to identifying family factors affecting handwashing practice. This study investigated the entire group of sixth-grade students (N = 2323) and their parents (N = 2089) at 11 elementary schools randomly selected from the Seoul Metropolitan Area, Korea. The results show that parents' handwashing practice, parent and child bonding, and shared time have a significant correlation with child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…The pursuit of healthy living has been associated with the ''logic of choice'' (Mol 2008), which refers to a mode of organizing perspectives and actions and of understanding the relationship between individuals, environments, and daily lives, as well as dealing with knowledge and practices of being healthy. Empirical studies have shown that healthrelated habits and perceptions attained through healthy living in a family enable children to develop everyday healthy practices that significantly affect their health outcomes (Song et al 2013;Turney et al 2013;van Grieken et al 2014) and quality of life (Dwyer et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The pursuit of healthy living has been associated with the ''logic of choice'' (Mol 2008), which refers to a mode of organizing perspectives and actions and of understanding the relationship between individuals, environments, and daily lives, as well as dealing with knowledge and practices of being healthy. Empirical studies have shown that healthrelated habits and perceptions attained through healthy living in a family enable children to develop everyday healthy practices that significantly affect their health outcomes (Song et al 2013;Turney et al 2013;van Grieken et al 2014) and quality of life (Dwyer et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, participants in the study also believed that hand hygiene behaviour should start early in life. A study in Seoul, Korea [38], conducted in an elementary school setting with Year 6 students, showed parents' handwashing practice, parent and child bonding, and shared time have a significant correlation with children's hand hygiene practice. Our study also suggested that both PCPs and parents thought hand hygiene practice should start with good role modelling in the home, with frequent reminders.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas 67.7% of participants' mother's had primary school education and 32.3% had high school education, 53.8% of their father's had primary school or lower education and 46.3% had high school or higher education [ Table 2]. Song et al [20] investigated that how family factors affect hand-washing habits, and they indicated that family's high education level affects kids to wash their hands more precisely who already have handwashing habit. Previous studies showed that family factor is effective on children's health behaviors, and families are role model for developing emotions, behaviors, and thoughts in their children.…”
Section: Discussionmentioning
confidence: 99%